How and when do mobile media demands impact well-being? Explicating the Integrative Model of Mobile Media Use and Need Experiences (IM³UNE) - Schneider, Frank M.; Lutz, Sarah; Halfmann, Annabell; Meier, Adrian; Reinecke, Leonard (Mobile Media and Communication, 2022)
Using mobile media can be both detrimental and beneficial for well-being. Thus, explaining how and when they elicit such effects is of crucial importance. To explicate boundary conditions and processes for digital well-being, this article introduces the Integrative Model of Mobile Media Use and Need Experiences IM³UNE. Instead of assuming mobile media to be pathogenic, the IM³UNE offers a salutogenic perspective-it focuses on how we can stay healthy when using mobile media ubiquitously in daily life. More specifically, the model assumes that both the satisfaction and the frustration of basic psychological needs are key underlying mechanisms linking demanding mobile media use to well-being. However, the impact of these mechanisms is contingent on how users perceive, appraise, act on, and make sense of mobile media demands according to their global orientation to life (i.e., their sense of coherence, SOC). Integrating prior work, we theoretically link mindfulness, self-control, and meaningfulness to SOC's central facets, arguing that they represent crucial personal resources required to cope with mobile media demands. Thus, the offers an integrative framework, guiding further research towards a more nuanced study of mobile media's effect on well-being.
CRIS-Team WoS Importer:2021-12-03